Analysis of two-particle transfer reaction in the 18O+40Ca and 20Ne+116Cd collisions. (1st March 2023) - Ferreira, J. L.; Lubian, J.; Cardozo, E. N.; Cappuzzello, F.; Cavallaro, M.; Carbone, D.; ,
Abstract: Two-neutron and two-proton transfer reactions have been analyzed in the present work. These kind of transfer reactions is an excellent tool to get insights into the short-range correlations on nucleons in a nuclear state. The direct and sequential two-particle transfer mechanisms, for which the valence particles can be transferred, were compared one with other to probe the populated nuclear states. Large-scale shell model calculations were performed to obtained the spectroscopic amplitudes for one and two valence particles.